Successive 1-Month Weight Increments in Infancy Can Be Used to Screen for Faltering Linear Growth. Issue 12 (14th October 2015) - Onyango, Adelheid W; Borghi, Elaine; de Onis, Mercedes; Frongillo, Edward A; Victora, Cesar G; Dewey, Kathryn G; Lartey, Anna; Bhandari, Nita; Baerug, Anne; Garza, Cutberto
Abstract: Background: Linear growth faltering in the first 2 y contributes greatly to a high stunting burden, and prevention is hampered by the limited capacity in primary health care for timely screening and intervention. Objective: This study aimed to determine an approach to predicting long-term stunting from consecutive 1-mo weight increments in the first year of life. Methods: By using the reference sample of the WHO velocity standards, the analysis explored patterns of consecutive monthly weight increments among healthy infants. Four candidate screening thresholds of successive increments that could predict stunting were considered, and one was selected for further testing. The selected threshold was applied in a cohort of Bangladeshi infants to assess its predictive value for stunting at ages 12 and 24 mo. Results: Between birth and age 12 mo, 72.6% of infants in the WHO sample tracked within 1 SD of their weight and length. The selected screening criterion ("event") was 2 consecutive monthly increments below the 15th percentile. Bangladeshi infants were born relatively small and, on average, tracked downward from approximately age 6 to <24 mo (51% stunted). The population-attributable risk of stunting associated with the event was 14% at 12 mo and 9% at 24 mo. Assuming the screening strategy is effective, the estimated preventable proportion in the group who experienced the event would be 34% at 12 mo and 24% at 24 mo. Conclusions: This analysis offers an approach for frontline workers to identify children at risk of stunting, allowing for timely initiation of preventive measures. It opens avenues for further investigation into evidence-informed application of the WHO growth velocity standards.